2020
DOI: 10.1049/iet-sen.2019.0149
|View full text |Cite
|
Sign up to set email alerts
|

Software defect prediction via LSTM

Abstract: Software quality plays an important role in the software lifecycle. Traditional software defect prediction approaches mainly focused on using hand-crafted features to detect defects. However, like human languages, programming languages contain rich semantic and structural information, and the cause of defective code is closely related to its context. Failing to catch this significant information, the performance of traditional approaches is far from satisfactory. In this study, the authors leveraged a long sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 32 publications
(37 reference statements)
0
36
0
Order By: Relevance
“…Subsequently, they extracted semantic features from source code changes and extended change-level defect prediction [ 16 ]. Deng et al [ 17 ] proposed a defect-prediction framework based on bidirectional long short-term memory network (Bi-LSTM). The long-distance dependence of Bi-LSTM can better learn contextual semantic features in long-sequence data.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, they extracted semantic features from source code changes and extended change-level defect prediction [ 16 ]. Deng et al [ 17 ] proposed a defect-prediction framework based on bidirectional long short-term memory network (Bi-LSTM). The long-distance dependence of Bi-LSTM can better learn contextual semantic features in long-sequence data.…”
Section: Related Workmentioning
confidence: 99%
“…Compared with coarse-grained prediction, fine-grained methods can render software testing more reasonable when allocating resources. Recent studies in Java software have shown that the file-level prediction model is more effective than that of the package-level [17][18][19][20][21][22], and the method-level [23][24][25] prediction model is more effective than those of the package-level and file-level. Pascarella et al [25] used different systems and periods to replicate the research of Giger et al [26] on method-level bug prediction, and they analysed the defect-prediction performance under actual conditions.…”
Section: Defect Prediction Based On Fine-grained Analysismentioning
confidence: 99%
“…Unlike designed top-down hand-crafted features, the features are generated bottom-up from the source code, which could represent structural and semantics information of the source code. Recently, many deep learning models, including Deep Belief Networks [4,15], CNN [5][6][7]10,17,19,24,25], LSTM [11,12,14,16,18], Transformers [8], and other deep learning models [13,22] are used in software defect prediction.…”
Section: Deep Transfer Learningmentioning
confidence: 99%
“…The results showed that the proposed framework improved Precision by 4.8%, Recall by 2.4% and F-measure by 8.5% on average. Dam et al (2019) proposed the deep tree-based LSTM model, the model took a raw AST of a source file to be used as input. The model used two classifiers (LR and Random Forest (RF) Zhang et al, 2018a), to choose the best one of them.…”
Section: E Frameworkmentioning
confidence: 99%